Transportation of hydrogen and natural gas mixtures in pipelines: review of recent literature - Romero, Oldrich Joel; Barbosa, Isabel (Latin American Journal of Energy Research, 2025)
This study presents a bibliometric review on the transport of hydrogen–natural gas mixtures through pipelines. The objective is to identify research trends, main contributors, and scientific gaps related to hydrogen blending as a strategy to support the energy transition. The analysis used a quantitative approach based on bibliometrics, employing the Bibliometrix package in R Studio to process data extracted from Scopus and Web of Science databases between 2020 and 2025. The Methodi Ordinatio equation was applied to rank the most relevant publications. Results show a significant growth in research on hydrogen transport through existing gas infrastructure, with China leading global scientific production. The International Journal of Hydrogen Energy stands out as the main publication source. Challenges such as hydrogen embrittlement, material compatibility, and transport costs remain barriers to large-scale implementation. This review contributes by mapping key actors, regions, and knowledge gaps, highlighting the need for future research integrating life-cycle analysis and material integrity studies to ensure safe and cost-effective hydrogen blending in pipeline networks.
Keywords: hydrogen blending